Ibm Pelatihan Pembuatan Stik Daun Kelor Sebagai Makanan Ringan Kaya Vitamin Dan Antioksidan Bagi Kelompok Mitra Di Desa Borisallo Kecamatan Parangloe Kabupaten Gowa - Niniek F Lantara; Arfah, Aryati; Munawir Nasir (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The target of this IbM program is the Partner Group in Gowa Regency (Pesantren Wihdatul Ulum Borisallo Gowa). The IbM program to be developed is the Making of Moringa Leaf Sticks using moringa leaves as raw materials along with other additional ingredients. The advantages of these Moringa Leaf Sticks are as a tasty and nutritious snack containing various vitamins and antioxidants. Moringa Leaf Sticks use raw materials such as wheat flour and moringa leaves, which are readily available. Moringa leaves are easy to cultivate, making them readily accessible. In addition, Moringa Leaf Sticks can be made with simple technology and basic equipment, making it easy to be developed by the Partner Group in Gowa Regency, turning it into a new entrepreneurial venture that can increase income and improve the community's economy. These Moringa Leaf Sticks have the potential to be marketed in stores as they are generally liked by the public and can contribute to improving public health